Limited risks of major congenital anomalies in children of mothers with IBD and effects of medications - Ban, Lu; Tata, Laila J.; Fiaschi, Linda; Card, Timothy R. (Elsevier, 2014)
Background & aims: Concerns persist about the risk of major congenital anomalies in children of women with inflammatory bowel disease (IBD), and whether medication use affects risk. We assessed these risks, and variations in use of medications by women with IBD before, during, and after pregnancy.